2020
DOI: 10.1371/journal.pone.0240227
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortical activity elicited by infrared laser irradiation from the outer ear in Mongolian gerbils

Abstract: Infrared neural stimulation has been studied for its potential to replace an electrical stimulation of a cochlear implant. No studies, however, revealed how the technic reliably evoke auditory cortical activities. This research investigated the effects of cochlear laser stimulation from the outer ear on auditory cortex using brain imaging of activity-dependent changes in mitochondrial flavoprotein fluorescence signal. An optic fiber was inserted into the gerbil's ear canal to stimulate the lateral side of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 57 publications
(74 reference statements)
2
12
0
Order By: Relevance
“…This notion is partially compatible with our findings (Fig. 1B) that show that cochlear laser stimulation can produce a CAP without a clear CM response, as reported in earlier studies (Izzo et al, 2006;Tamai et al, 2019;Tamai et al, 2020;Teudt et al, 2011). These findings suggest that laser treatment can produce an auditory response in individuals with profound hearing loss who require cochlear implants.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This notion is partially compatible with our findings (Fig. 1B) that show that cochlear laser stimulation can produce a CAP without a clear CM response, as reported in earlier studies (Izzo et al, 2006;Tamai et al, 2019;Tamai et al, 2020;Teudt et al, 2011). These findings suggest that laser treatment can produce an auditory response in individuals with profound hearing loss who require cochlear implants.…”
Section: Discussionsupporting
confidence: 93%
“…The repetition rate of the laser stimuli was 100 Hz. The laser was presented 100 times via an optical fiber (diameter, 100 μm; NA, 0.22) and inserted mediolaterally into the left outer ear canal using a micromanipulator (MM-3, Narishige, Tokyo, Japan) as described in earlier reports (Tamai et al, 2019;Tamai et al, 2020). The tip of stimulation fiber was set at around 0.7 mm in front of the tympanic membrane to ensure that the cochlea was irradiated transtympanically from the outer ear (Fig.…”
Section: Laser Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, INS has been extensively studied in the peripheral nervous system with successful applications in the auditory system 23 , 24 , in chronic neurostimulation applications 25 , in the vestibular and facial nerves 26 28 , and as a method for cardiac pacing 29 . The first application of INS in the central nervous system (CNS) was demonstrated by Cayce and colleagues in 2010 in thalamocortical brain slices 30 .…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that transtympanic laser stimulation from the outer ear could evoke a cochlear response, bypassing the middle ear function (Tamai, Horinouchi, Hiryu, & Kobayasi, 2019; Uenaka, Nagamura, Hiryu, Kobayasi, & Tamai, 2022). The auditory cortical activity elicited by transtympanic laser stimulation depends on stimulus intensity (Tamai et al, 2020). These results imply that a hearing prosthesis with infrared laser stimulation could be a noninvasive alternative to the conventional implantable auditory prosthesis.…”
Section: Introductionmentioning
confidence: 99%